2020
DOI: 10.1177/0049475520978174
|View full text |Cite
|
Sign up to set email alerts
|

Low serum potassium among patients with COVID-19 in Bangkok, Thailand: Coincidence or clinically relevant?

Abstract: Our cross-sectional study estimated the prevalence and clinical relevance of hypokalaemia among confirmed COVID-19 cases admitted in three hospitals in Bangkok during the early outbreak in Thailand. Of 36 patients, nine were in the hypokalaemia group (25%) and 27 in the normokalaemia group (75%). All cases were asymptomatic, and 94.4% had mild hypokalaemia. Hypokalaemia was found significantly earlier in the course of COVID-19 without evidence of significant extrarenal potassium loss. Body temperature and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…However, we specifically collected detailed data on vital signs including respiratory rate, albumin status, serum sodium, potassium and renal function, total leukocyte counts and subsets including neutrophils and lymphocytes, and coagulation profiles. This was in keeping with our hypothesis and aims and based on emerging literature linking these characteristics with morbidity and mortality in COVID-19 [15] , [16] , [17] , [18] , [19] , [20] . Demographic, clinical and laboratory data were extracted using computer search algorithms from electronic medical records and by the investigators from paper case notes.…”
Section: Subjects Materials and Methodssupporting
confidence: 80%
“…However, we specifically collected detailed data on vital signs including respiratory rate, albumin status, serum sodium, potassium and renal function, total leukocyte counts and subsets including neutrophils and lymphocytes, and coagulation profiles. This was in keeping with our hypothesis and aims and based on emerging literature linking these characteristics with morbidity and mortality in COVID-19 [15] , [16] , [17] , [18] , [19] , [20] . Demographic, clinical and laboratory data were extracted using computer search algorithms from electronic medical records and by the investigators from paper case notes.…”
Section: Subjects Materials and Methodssupporting
confidence: 80%
“…A numbers of studies have reported hypokalemia as an important clinical manifestation of this new coronavirus 14,19,21,47–49 . Chen et al.…”
Section: Potassium Disorders and Infectious Diseasesmentioning
confidence: 99%
“…One study measured electrolyte levels at COVID-19 diagnosis and one study recorded the imbalance at any time during hospitalization. [20,48] As some studies measured electrolyte levels beyond 24 hours, [14,22,47,54] we excluded them in sensitivity analyses. This did not did not alter our conclusions.…”
Section: Definitions Of Electrolyte Imbalancesmentioning
confidence: 99%
“…[14,21,39] Dyskalemia Nine and two studies investigated the association of hypokalemia and hyperkalemia with the same COVID-19 outcomes respectively (Table 1). [20,23,24,40,44,[46][47][48]52] Majority of studies defined hypokalemia and hyperkalemia as having a serum potassium level of < 3.5 mmol/L or > 5.1 mmol/L respectively. Three studies further stratified their sample based on hypokalemia severity.…”
Section: Dysnatremiamentioning
confidence: 99%
See 1 more Smart Citation